Matrix metalloproteinases inhibition promotes the polyfunctionality of human natural killer cells in therapeutic antibody‐based anti‐tumour immunotherapy. (6th June 2013) - Zhou, Q.; Gil‐Krzewska, A.; Peruzzi, G.; Borrego, F.
Summary Activation of human natural killer (NK) cells is associated with the cleavage of CD16 from the cell surface, a process mediated by matrix metalloproteinases (MMPs). In this report, we examined whether inhibition of MMPs would lead to improved NK cell antibody‐dependent cell‐mediated cytotoxicity (ADCC) function. Using an in‐vitro ADCC assay, we tested the anti‐tumour function of NK cells with three different therapeutic monoclonal antibodies (mAbs) in the presence of MMPs inhibitor GM6001 or its control. Loss of CD16 was observed when NK cells were co‐cultured with tumour targets in the presence of specific anti‐tumour antibodies, and was found particularly on the majority of degranulating NK responding cells. Treatment with MMPs inhibitors not only prevented CD16 down‐regulation, but improved the quality of the responding cells significantly, as shown by an increase in the percentage of polyfunctional NK cells that are capable of both producing cytokines and degranulation. Furthermore, MMPs inhibition resulted in augmented and sustained CD16‐mediated signalling, as shown by increased tyrosine phosphorylation of CD3ζ and other downstream signalling intermediates, which may account for the improved NK cell function. Collectively, our results provide a foundation for combining MMPs inhibitors and therapeutic mAbs in new clinical trials for cancer treatment.